2015
DOI: 10.1080/13576275.2015.1012489
|View full text |Cite
|
Sign up to set email alerts
|

Problems with the coronial determination of ‘suicide’

Abstract: After over 100 years of constant dissatisfaction with the accuracy of suicide data, this paper suggests that the problem may actually lie with the category of suicide itself. In almost all previous research, 'suicide' is taken to be a self-evidently valid category of death, not an object of study in its own right. Instead, the focus in this paper is upon the presupposition that how a social fact like suicide is counted depends upon norms for its governmental regulation, leading to a reciprocal relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…Part of the problem for coroners is balancing the competing demands of accurate manner of death findings with the need for care and sensitivity toward the family. In suicide verdicts, these are made more complicated by the difficulty of determining intent in the context of a highly stigmatised death and the various and varying definitions of suicide that currently exist [ 29 ]. There is thus significant ambiguity or “wriggle room” in a finding of suicide, ambiguity that is also acknowledged in the literature [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the problem for coroners is balancing the competing demands of accurate manner of death findings with the need for care and sensitivity toward the family. In suicide verdicts, these are made more complicated by the difficulty of determining intent in the context of a highly stigmatised death and the various and varying definitions of suicide that currently exist [ 29 ]. There is thus significant ambiguity or “wriggle room” in a finding of suicide, ambiguity that is also acknowledged in the literature [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is no standard definition of suicide deployed across all Australian jurisdictions [ 25 ]. This is perhaps not surprising given the range of definitions in use across the literature [ 29 ]. The definitions used in the Australian coronial context appear to have been taken from a variety of sources—civil law, dictionaries, ‘common sense’, academic texts, internal memos and bench-books [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the importance of suicide statistics, this may require targeted changes to coronial legislation and practice. A number of speculative suggestions can be made here (Tait, Carpenter, De Leo and Tatz, 2015). For example, rather than a single binarysuicide / not suicideit has been suggested that graded determinations of suicide could be more effective (De Leo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy and quality of coronial data have been the subject of ongoing debate with researchers claiming significant underestimations in suicide deaths [72]. The range and quality of coronial data due to missing data from many case reports also varies across jurisdictions.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%